Uguali e diversi: un’indagine comparativa tra generazioni sulle attese e le percezioni relative alla genitorialità - Natoli, Silvia; Batini, Federico; Toti, Giulia (Rivista Italiana di Educazione Familiare, 2016)
This paper, following an analysis of the literature and taking some key concepts related to parenting, highlights the possible transmissive relationships on perception related to parenting style, through a qualitative research conducted in the Umbrian territories and Tuscany. The intent was to access, through semi-structured interview, to the prospect of the subject, accepting his point of view, his interpretations of the theme and perceptions regarding personal experience. The aim was to see if and how the perception of the “aggregate” parental style adopted by their primary caregivers, influence the reflection and perception level of the educational model that is adopted (in the case of couples already with children) or that is intended to take (in the case of those surveyed whom are not yet parents), towards their children. The research was aimed to highlight any differences arising in connection with such perception among those who already play the parental role and those not yet parents. Thus, is there a perception of intergenerational transmission of educational styles? How these perceptions influence the practices? The style of education experienced as children, will influence or is influencing the way of being a parent and the choice of parenting style?